Conditions for an efficient innovation process: The complementarity between new HRM practices and suggestion schemes - Mihai Paunescu (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2005)
The specific and tacit knowledge of shopfloor employees are vital sources for innovative work behaviour. Firms can use these skills to increase the efficiency of process innovation in the stages of idea generation and implementation of new processes. This study examines the necessary conditions for harnessing employees' innovative capabilities. The first condition is the emphasis on the human resource practices that support the formation, utilization and transfer of specific knowledge. As a second condition, organizations must adopt continuous improvement practices which capitalize on the developed specific knowledge. I use the Changing Employment Relationships survey to test for the complementary relationship between such a specific set of human resource practices and the existence of a suggestion scheme. The results confirm that organizations which provide the framework for their employees to acquire inventive skills will be more likely to establish a suggestion scheme. Secondly, the more practices are utilized the more attractive the suggestion scheme is for the employees to submit proposals. One reason therefore is due to greater efforts in the design of the suggestion scheme.
Keywords: O31; M54; M12; 330; suggestion schemes; innovative work behaviour; user innovation; organizational learning; tacit knowledge; kaizen; continuous improvement